Potensi Nilai Ekonomi Pemanfaatan Limbah Sapi Perah dan Kontribusinya terhadap Pendapatan Peternak - Putra, Orlanda Mahari; Mahardika, Muhammad Naufal; Herlina, Linda; Firman, Achmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This research was conducted among members of the Nagrak Asih Mandiri livestock group in Sukajaya Village, Lembang Subdistrict, West Bandung Regency, West Java Province. This study aims to analyze dairy cattle business income, income from waste utilization, contribution of waste utilization to dairy cattle business income, and the relationship between the number of livestock ownership with dairy cattle business income and income from waste utilization. This research was conducted using a survey method involving 30 respondents of livestock group members. The research location was determined purposively. Income analysis was conducted by calculating revenue and production costs including fixed costs and variable costs. The relationship between the number of livestock ownership with dairy cattle business income and income from waste utilization was analyzed with Pearson product moment correlation. The results showed that the average income of dairy cattle business was Rp. 8,644,176/ST/farmer/year, and the average income from waste utilization was Rp. 863,577/ST/farmer/year. The average contribution of income from waste utilization to dairy cattle business income is 1.86%/ST. The results of the correlation analysis showed a low positive relationship between the number of livestock ownership and income from waste utilization (r=0.324). The number of livestock ownership with the main income of dairy cattle farming is moderately related (r=0.547).